2017
DOI: 10.3892/ijmm.2017.2953
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive role of diallyl trisulfide in the activated platelet-mediated hematogenous metastasis of MDA-MB-231 human breast cancer cells

Abstract: Accumulating evidence has indicated that garlic consumption may reduce the risk of developing several types of cancer, and extensive studies have revealed the effects of its bioactive component, diallyl trisulfide (DATS), on the proliferation and apoptosis of tumor cells. The present study was undertaken to examine whether DATS affects hematogenous metastasis. In view of the dynamic crosstalk interplayed by tumor cells and platelets in hematogenous metastasis, we attempted to demonstrate the role of DATS in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…6,7 It was also found that DATS suppressed metastasis by reducing the levels of a series of inflammatory factors, such as the tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), limiting the remodeling of the extracellular matrix in the tumor microenvironment (TME), and diminishing hypoxia-induced tumor angiogenesis. 8,9 Despite the fact that DATS possesses potent antimetastatic activity, there has been no efficient carrier to deliver it to tumor sites in vivo. An array of nanodrug delivery systems with targeting technologies have been used to create DATS formulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 It was also found that DATS suppressed metastasis by reducing the levels of a series of inflammatory factors, such as the tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), limiting the remodeling of the extracellular matrix in the tumor microenvironment (TME), and diminishing hypoxia-induced tumor angiogenesis. 8,9 Despite the fact that DATS possesses potent antimetastatic activity, there has been no efficient carrier to deliver it to tumor sites in vivo. An array of nanodrug delivery systems with targeting technologies have been used to create DATS formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur-containing compounds such as diallyl trisulfide (DATS) isolated from garlic have attracted great attention for their antitumor effects. Previous studies demonstrated that DATS inhibited metastasis by decreasing the migration and invasion of tumor cells in various animal tumor models, such as breast cancer and melanoma models. , It was also found that DATS suppressed metastasis by reducing the levels of a series of inflammatory factors, such as the tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), limiting the remodeling of the extracellular matrix in the tumor microenvironment (TME), and diminishing hypoxia-induced tumor angiogenesis. , Despite the fact that DATS possesses potent antimetastatic activity, there has been no efficient carrier to deliver it to tumor sites in vivo . An array of nanodrug delivery systems with targeting technologies have been used to create DATS formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al. [ 92 ] found that DATS inhibits metastasis of BC cells by attenuating activated transforming growth factor-β1 signaling. Bauer et al.…”
Section: Allyl Sulfur Compounds In Garlicmentioning
confidence: 99%
“…Our previous studies showed that the release of TGF-β1 was significantly increased in the activated platelet-tumor cell co-culture system, and repression of TGF-β1 could dramatically retard the malignant biological progression of breast cancer cells, suggesting that TGF-β1 may act as a key molecule mediating the interactions between tumor cells and platelets [8]. It has been documented that Salvia miltiorrhiza exerts an important effect on enhancing immunity, which was evidenced by the fact that it boosted the killing activities of cytotoxic T lymphocytes (CTL) and NK cells and stimulated the phagocytosis of macrophages.…”
Section: Introductionmentioning
confidence: 99%